2021
DOI: 10.2196/25522
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive 6A Framework for Improving Patient Self-Management of Hypertension Using mHealth Services: Qualitative Thematic Analysis

Abstract: Background Hypertension affects over 15% of the world’s population and is a significant global public health and socioeconomic challenge. Mobile health (mHealth) services have been increasingly introduced to support hypertensive patients to improve their self-management behaviors, such as adherence to pharmacotherapy and lifestyle modifications. Objective This study aims to explore patients’ perceptions of mHealth services and the mechanisms by which th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
2
11
0
1
Order By: Relevance
“…The results also support the importance of providing feedback to patients about their health status that is reflected by the vital signs they uploaded in mHealth services [ 8 ]. Awareness of their own health status, particularly if the disease is deteriorating, will drive them to formulate an intention to continuously use the mHealth services.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The results also support the importance of providing feedback to patients about their health status that is reflected by the vital signs they uploaded in mHealth services [ 8 ]. Awareness of their own health status, particularly if the disease is deteriorating, will drive them to formulate an intention to continuously use the mHealth services.…”
Section: Discussionsupporting
confidence: 59%
“…With increasing awareness and ability, patients are motivated to self-manage their behavior, that is, adhere to treatment, thereby controlling their chronic conditions and maintaining the quality of life. When used over a long period of time, these apps are likely to result in positive outcomes such as obvious changes in health behaviors [ 6 - 8 ]. Despite their potential benefits, mHealth apps are rarely used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate the necessity for additional research into the end-user’s aspect and preferences to discover which features and delivery mechanisms are most beneficial. In this regard, qualitative research provides opportunities to explore end-user’s experiences and get detailed information about how they perceive user engagement via in-depth interviews (Song et al, 2021). Therefore, the end-user’s usage of mHealth applications and the behavioral approach’s mechanism to utilize mHealth continue to be debated and require more research (Glomsås et al, 2021; Tajudeen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the use of health information technology is useful in improving hypertension management (19)(20)(21). However, better use of health information technology and identi cation of motivating and inhibiting factors that affect the use of technology is important (22,23).…”
Section: Summary Of Findingsmentioning
confidence: 95%